Evaluation of the Income Convergence Hypothesis in Ten New Members of the European Union. A Panel Unit Root Approach - Reza, Ranjpour; Zahra, Karimi Takanlou (Panoeconomicus, 2008)
In this paper, different tests of unit root in panel data are implemented for studying real economic convergence and catching-up in ten new members of European Union (EU) toward average EU per capita income and average of ancient members. We used the "EuroStat" quarterly real per capita output data on the period 1995 - 2005. The results support existence of absolute convergence and catching-up processes in sample countries towards EU standards.Key words: Growth, European Union, Convergence, Panel unit root, Catching-up.JEL: C12, C33, O47, O52.